Insulin-induced mTOR signaling and gluconeogenesis in renal proximal tubules: A mini-review of current evidence and therapeutic potential - Nakamura, Motonobu; Satoh, Nobuhiko; Horita, Shoko; Nangaku, Masaomi (Frontiers in Pharmacology, 2022)
Energy is continuously consumed in the living body, and gluconeogenesis maintains glusose homeostasis during starvation. Gluconeogenesis occurs in the liver and kidneys, with the proximal tubule being the main source of renal gluconeogenesis, which accounts for up to 25% and 60% of endogenous glucose production during fasting and after a meal, respectively. Mechanistic target of rapamycin (mTOR), which exists downstream of the insulin pathway, plays an important role in regulating proximal tubular gluconeogenesis. mTOR is an atypical serine/threonine kinase present in two complexes. mTORC1 phosphorylates substrates that enhance anabolic processes such as mRNA translation and lipid synthesis, and catabolic processes such as autophagy. mTORC2 regulates cytoskeletal dynamics and controls ion transport and proliferation via phosphorylation of SGK1. Thus, mTOR signaling defects have been implicated in various pathological conditions, including cancer, cardiovascular disease, and diabetes; however, concrete elucidations of the associated mechanisms are still unclear. This review provides an overview of mTOR and a description of the relationship between mTOR and renal tubular gluconeogenesis in glucose metabolism.